2022
DOI: 10.7759/cureus.28178
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Trends and Clinical Characteristics of Childhood Leukemia in Saudi Arabia: A Review

Abstract: Leukemia is the most prevalent type of cancer among children in Saudi Arabia. It has variable clinical presentations and accounts for a large scale of mortality and morbidity. Acute lymphoblastic leukemia (ALL) constituted the majority of pediatric leukemic cases with male gender predisposition. The most common first presentation that patients come with are manifestations of anemia, thrombocytopenia, and fever. Bone pain, fatigue, weight loss, organomegaly, and pale skin are among the commonest manifestations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…A recent study analyzed the epidemiological trend of childhood leukemia in Saudi Arabia and discovered that the Riyadh region has the greatest prevalence of childhood leukemia with 578 )28.6%( cases while the Al-Madinah Al-Munawwarah region ranks fifth with 142 )7%( cases. 7 By comparing the epidemiological trend of childhood leukemia cases in the Al-Madinah Al-Munawwarah region between 1999 and 2008 to our observations obtained between 2016 and 2022, we found a 16.9% rise in the epidemiological trend of leukemia cases in the region.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…A recent study analyzed the epidemiological trend of childhood leukemia in Saudi Arabia and discovered that the Riyadh region has the greatest prevalence of childhood leukemia with 578 )28.6%( cases while the Al-Madinah Al-Munawwarah region ranks fifth with 142 )7%( cases. 7 By comparing the epidemiological trend of childhood leukemia cases in the Al-Madinah Al-Munawwarah region between 1999 and 2008 to our observations obtained between 2016 and 2022, we found a 16.9% rise in the epidemiological trend of leukemia cases in the region.…”
mentioning
confidence: 53%
“…6 In contrast, in accordance with the regional distribution of childhood leukemia in Saudi Arabia from 1999 to 2008, the overall number of leukemic cases was 2021, with the Al-Madinah Al-Munawwarah region having 142 )7%( cases among all regions, making it more prevalent than some other regions. 7 The present study aimed to provide an updated estimate to the prevalence of pediatric hematological malignancies in the Al-Madinah Al-Munawwarah region, Kingdom of Saudi Arabia between 2016 and 2022 using data that was compiled from an authoritative database of the Maternity and Children's Hospital, King Salman Medical City, Al-Madinah Al-Munawwarah, Saudi Arabia.…”
mentioning
confidence: 99%
“…Research conducted at Hasan Sadikin Hospital showed that the clinical manifestations that often appeared were paleness, hepatomegaly, and fever [10]. A systematic review and meta-analysis study by Clarke at al (2016) showed that the five most common symptoms in >50% of ALL children were hepatomegaly, splenomegaly, pallor, fever, and bruising [16] Meanwhile, a study in Saudi Arabia showed that the most common symptoms in ALL children were fever, fatigue, bone pain, paleness, weight loss, and decreased consciousness [17].…”
Section: Resultsmentioning
confidence: 99%
“…This places leukemia as the 13 most prevalent cancer type worldwide. 4 The incidence of leukemia in Saudi Arabia likewise exhibited an upward trend over the period of 1999 to 2013, with a total of 8,712 cases reported for both genders. According to the data from the Saudi Cancer Registry (SCR), the majority of patients diagnosed with leukemia were male (57.2%), with 42.8% being female.…”
mentioning
confidence: 99%